IMPLEMENTASI MODEL PEMBELAJARAN QUESTIONING UNTUK MENGOPTIMALKAN KEAKTIFAN BELAJAR SISWA DALAM PEMBELAJARAN (IPS) DI KELAS IV SDN GUMPANG 01 KARTASURA TAHUN PELAJARAN 2015/2016 - Waffak, Muhammad Nasihul (2016)
The study aims to review the husband Researchers purpose to review the implementation of the learning model describes questioned for review optimize student learning activeness hearts ips learning in class IV SDN Gumpang 01 Kartasura and researchers want to find a solution for the problem of optimizing the review of student learning activeness hearts ips learning in class IV SDN Gumpang 01 Kartasura. Research husband is a research experiment, for instance hearts research husband is grade IV SDN Gumpang Kartasura 01 academic year 2015/2016. Data collection techniques used that is interview, observation, and documentation. Data analysis technique used the reduction is to review select data protege the active and passive learning the learning model ips hearts with question. Conclusion hearts husband research is: (1) with students learning media uses most big hearts come on and enthusiastic learning IPS. (2) model with the student learning questioning students hooked to ask. Keywords: Learning Questioning, Optimization of Motivation and Learning IPS